2004
DOI: 10.1139/x04-103
|View full text |Cite
|
Sign up to set email alerts
|

Automatic thresholding for digital hemispherical photography

Abstract: This paper proposes an automatic thresholding method for the discrimination of sky and canopy elements in color hemispherical photographs taken with a digital camera (Nikon Coolpix 950). The exposures for photography were principally determined on the basis of zenith luminance. DIF photo , which is diffuse transmittance calculated from the hemispherical photographs, was related to DIF sensor , which is diffuse transmittance measured directly with a photosynthetic photon flux density sensor. First, the threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 19 publications
2
43
2
7
Order By: Relevance
“…In this way, the suitability of any given threshold could be examined in a "determination" stage and canopy then analysed using that threshold in a "quantification" stage. Theoretically, it should be possible to automate the determination stage, either fully or partially, using thresholdselection algorithms, and there have been several attempts to do this (e.g., [41,42]). However, these algorithms are not always successful in determining an appropriate threshold [43], especially when the relative contrast between vegetation and sky changes across the image (e.g., sun-illuminated vegetation against white cloud in one part of the image and shaded vegetation against bright blue sky in another part of the image) [44] and add substantially to processing time.…”
Section: Developing the Digital Image Analysis Techniquementioning
confidence: 99%
“…In this way, the suitability of any given threshold could be examined in a "determination" stage and canopy then analysed using that threshold in a "quantification" stage. Theoretically, it should be possible to automate the determination stage, either fully or partially, using thresholdselection algorithms, and there have been several attempts to do this (e.g., [41,42]). However, these algorithms are not always successful in determining an appropriate threshold [43], especially when the relative contrast between vegetation and sky changes across the image (e.g., sun-illuminated vegetation against white cloud in one part of the image and shaded vegetation against bright blue sky in another part of the image) [44] and add substantially to processing time.…”
Section: Developing the Digital Image Analysis Techniquementioning
confidence: 99%
“…Lhotka and Loewenstein [13] suggested that the measurements were made under overcast conditions, usually in the late morning hours. The digital images were processed based on a procedure developed by Ishida [18]. All images were analyzed to calculate the percentage of diffuse light intensity under the canopy (SOC percentage) using RGBFisheye ver.2.01 (Gifu, Japan).…”
Section: Measurement Of Light Intensity Under Tree Canopymentioning
confidence: 99%
“…The solar constant was defined as 1.370 W/m 2 , 0.6 was set for atmospheric transmissivity and 0.15 for the proportion of diffuse radiation compared to the calculated direct potential radiation. An automatic thresholding method based on the same color scheme was applied for the discrimination between sky and canopy elements in all digital photographs, as thresholding of the photographs is crucial and may significantly affect the calculated parameters [23]. The analysis was carried out for 120-degree angle of hemisphere, as it proved to be the best explaining angle [24].…”
Section: Assessment Of Crown Conditionsmentioning
confidence: 99%